2020
DOI: 10.1002/macp.201900302
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Naphthalene and Its Derivatives‐Based Microporous Organic Hyper‐Cross‐Linked Polymers via Different Methodologies

Abstract: A series of cost‐effective hyper‐cross‐linked polymers (HCLPs) are synthesized from naphthalene via the external cross‐linker (ECL) knitting method, the solvent knitting method, and the Scholl coupling reaction, respectively. According to multiple characterizations, the resulting polymers are thermally stable and fluorescent with large specific surface areas (SSAs) and narrow pore distributions. In particular the HCLP synthesized using dimethoxymethane as the ECL exhibits SSAs up to 2870 m2 g−1 and shows a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…HCLP 4 exhibited an amorphous structure as displayed by unordered small flake particle accumulation (Figure b), far different from accumulated spherical HCLPs 1–3. The substituted or heteroatom-doped raw materials (quinoline) failed to grow into characteristic spherical particles, which was due to the strong polarity-initiated complete destruction during the hyper-cross-linking process . Several weight loss stages of HCLP 4 were observed (Figure c) and the main weight loss occurred at 450–580 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCLP 4 exhibited an amorphous structure as displayed by unordered small flake particle accumulation (Figure b), far different from accumulated spherical HCLPs 1–3. The substituted or heteroatom-doped raw materials (quinoline) failed to grow into characteristic spherical particles, which was due to the strong polarity-initiated complete destruction during the hyper-cross-linking process . Several weight loss stages of HCLP 4 were observed (Figure c) and the main weight loss occurred at 450–580 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The substituted or heteroatom-doped raw materials (quinoline) failed to grow into characteristic spherical particles, which was due to the strong polarity-initiated complete destruction during the hyper-cross-linking process. 25 Several weight loss stages of HCLP 4 were observed (Figure 6c) and the main weight loss occurred at 450−580 °C. Total weight losses of less than 30% even at 900 °C indicated that HCLP 4 featured greater thermal stability than HCLPs 1−3.…”
Section: Effect Of Different N-doping Modificationmentioning
confidence: 97%
“…Moreover, the carbon yield of HCLPs can reach 60% even at 1000 °C, implying that HCLPs are suitable and promising precursors for carbon materials. 24 The microscopic morphology and structure of the HCs were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). As shown in Figure 2a−c, the HCs are large irregular particles formed by crosslinking and stacking of small particles of around 100 nm (Figure S2a−c).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the oxygen-to-carbon atomic ratio decreases as the pyrolysis temperature increases, indicating that the temperature is a critical factor in determining the oxygen content (Table ). Moreover, the carbon yield of HCLPs can reach 60% even at 1000 °C, implying that HCLPs are suitable and promising precursors for carbon materials …”
Section: Resultsmentioning
confidence: 99%
“…Hyper-crosslinked polymers (HCPs) are a kind of typical porous material initially reported by Davankov and co-workers in 1970s, and they have attracted increasing interest in recent years. , More recently, HCPs have achieved rapid development because of their diverse synthesis strategies, easy functionalization, high Brunauer–Emmett–Teller (BET) surface area ( S BET ), adjustable porosity, and diversified surface chemistry, , and they have been diffusely used in fields such as volatile organic compound adsorption, gas capture and separation, catalysis, ,, energy storage, and drug release …”
Section: Introductionmentioning
confidence: 99%